2019
DOI: 10.2147/copd.s188186
|View full text |Cite
|
Sign up to set email alerts
|

<p>Phenotyping and outcomes of hospitalized COPD patients using rapid molecular diagnostics on sputum samples</p>

Abstract: BackgroundEtiologies of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are heterogeneous. We phenotyped severe AECOPD based on molecular pathogen detection of sputum samples collected at hospitalization of COPD patients and determined their outcomes.MethodsWe phenotyped 72 sputum samples of COPD patients who were hospitalized with a primary diagnosis of AECOPD using a molecular array that detected common bacterial and viral respiratory pathogens. Based on these results, the patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Which streptococcal species are being identified in the Streptococcus cluster is therefore not known; use of species-specific PCR could resolve identity to the species level in future studies. 34 It should also be noted that sputum, although widely used in studies of the airway microbiome, has limitations in that it is often intermediate between bronchoalveolar lavage and upper airway swabs and therefore contains contributions from the upper and lower airway. Because our study aims to test the prognostic and phenotypic utility of the sputum microbiome, we make no inferences about lung ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Which streptococcal species are being identified in the Streptococcus cluster is therefore not known; use of species-specific PCR could resolve identity to the species level in future studies. 34 It should also be noted that sputum, although widely used in studies of the airway microbiome, has limitations in that it is often intermediate between bronchoalveolar lavage and upper airway swabs and therefore contains contributions from the upper and lower airway. Because our study aims to test the prognostic and phenotypic utility of the sputum microbiome, we make no inferences about lung ecology.…”
Section: Discussionmentioning
confidence: 99%
“…54 Among this population already in hospital with an acute exacerbation of COPD, the bacteriapositive subgroup had the best prognosis and the pathogen-negative group had the worst prognosis. 54 More recently, Prins et al reported the results of an RCT where CRP was used as a biomarker to direct antibiotic treatment in patients admitted to hospital with an acute exacerbation of COPD. Patients were randomized to receive biomarker directed antibiotic treatment if CRP was !50 mg/L (n ¼ 101) or guideline-based antibiotic treatment according to patient reported symptoms (n ¼ 119).…”
Section: Treatable Traits In Acute Exacerbationsmentioning
confidence: 95%
“…53 A further attempt to phenotype COPD patients using molecular microbiological techniques identified bacteria- and virus-positive groups or pathogen-negative patient groups. 54 Among this population already in hospital with an acute exacerbation of COPD, the bacteria-positive subgroup had the best prognosis and the pathogen-negative group had the worst prognosis. 54…”
Section: Treatable Traits: An Emerging Approach For Chronic Airway DImentioning
confidence: 95%
See 1 more Smart Citation
“…Mortality was ascertained through medical records and validated by death certificates. The detailed information about this study was previously published [ 16 ].…”
Section: Methodsmentioning
confidence: 99%